The Use and Abuses of Emulation as a Pedagogical Practice. Issue 3 (29th December 2017) - Jonas, Mark E.; Chambers, Drew W.
Abstract: From the late eighteenth through the end of the nineteenth century, educational philosophers and practitioners debated the benefits and shortcomings of the use of emulation in schools. During this period, "emulation" referred to a pedagogy that leveraged comparisons between students as a tool to motivate them to higher achievement. Many educationists praised emulation as a necessary and effective motivator. Other educationists condemned it for its tendency to foster invidious competition between students and to devalue learning. Ultimately, by the late nineteenth century emulation as a specific pedagogical practice had disappeared in American educational culture. In this article, Mark Jonas and Drew Chambers ask whether the disappearance of emulation is something to be celebrated or lamented. To answer this question they examine the historical concept of educational emulation and analyze the bases on which proponents and opponents argued. Parties on both sides of the debate framed their arguments in close relation to the way emulation was being used at that time, which prioritized actual competitions and prizes. In that context, the opponents made a better case, which presumably contributed to emulation's disappearance in schools afterwards. However, as earlier proponents of emulation argued, emulation need not be restricted to competitions and prizes. Instead, these proponents offered a philosophically and psychologically rich defense of emulation, but these were not carried through to an appropriate degree. The authors conclude that, construed appropriately, emulation not only had tremendous educational potential then, but still does today. With intentional effort on the part of teachers, emulation can greatly enrich students' lives and act as a powerful learning motivator.